PROTRUSIVE NATURE OF INTRUDING HYPERBAZIT MASSIVES IN THE SEVAN-AKERIAN OPHIOLITE ZONE (Proceedings of the YSU C: Geological and Geographical Sciences, 2015)
This article discusses the origin of ophiolits in the Sevan-Akerian zone from the point of view of classical theory of geosynclinal folded areas. The geological data confirm that over the Sevan-Akerian zone there is no evidence of the existence of oceanic crust rocks fragments, pulled over to the continent as a result of the closure of the ocean. Ophiolites are rocks of mantle origin, which have been crystallized and consolidated in the depths of subcrustal peridotitic melt, and subsequently intruded into deep faults in the form of a protrusion to the subsurface zone of the Earth's crust, bypassing oceanic situation. The term «ophiolite» should be used as the title of hyperbasites and not for the association of ultramafic rocks, gabbroids, volcanic and basaltic pillow lavas complex and deep-pelagic clays, as well as for siliceous (radiolaritic) sediments of the ocean floor.
Keywords: ophiolite; hyperbasite; protrusion; obduction; mantle; gabbroic complex